Spiders of Odisha: a preliminary checklist - Sudhir Ranjan Choudhury (Journal of Threatened Taxa, 2019)
The present checklist of spiders of Odisha is the result of the compilation of all published literature on spiders and primary data collected during the present study carried out from July 2016 to March 2017 in Odisha.  A total of 138 species of spiders belonging to 95 genera and 33 families were recorded in the present study.  Of which, seven families, 36 genera and 80 species of spiders were reported for the first time from Odisha.  Of these 80 species, 78 spider species were exclusively reported from the Eastern Ghats of Odisha. With this study, spider diversity of Odisha comprised of 248 species belonging to 139 genera and 39 families.  Whereas, Eastern Ghats of Odisha comprised of 181 species belonging to 109 genera and 35 families.  Of total spiders from Odisha, 23 species were found to be endemic to southern Asia, 49 species endemic to India and 19 species endemic to Odisha.